Convergence in institutions and market outcomes: crosscountry and time-series evidence from the BEEPS surveys in transition economies - Pradeep Mitra; Alexander Muravyev; Mark E. Schaffer (Deutsches Institut für Wirtschaftsforschung (DIW), 2008)
This paper uses the BEEPS firm-level data to study the process of convergence of transition countries with developed market economies. The primary focus of the study is on competition and market structure, finance and the structure of lending to firms, and how firms respond to the economic environment by restructuring; we are able to do this because the BEEPS cover thousands of firms from virtually all transition countries over a long time period (1996-99 through 2002-05), as well firms from developed market economies, thus providing a set of natural benchmarks. We find substantial evidence of convergence of transition countries with developed market economies in a number of dimensions. The pattern of growth at the country, sectoral and firm level shows rapid growth of the new private sector and of the micro- and small-firm sectors, with the size distribution of firms moving towards the pattern observed in the BEEPS surveys of developed market economies. Our interpretation of the evidence on competition is that there is an initial move by firms into niches to exploit local market power, and later in transition entry and domestic competitive pressure increases. In finance, the increasing reliance on retained earnings in transition countries reflects a maturation of the sector as new firms come to rely less on informal and family sources of finance. The scale of restructuring and innovation activity is as high or higher in transition economies as in developed market economies. Interestingly, we find evidence of an inverse-U shape pattern, with the peak of restructuring activity taking place in 2002, the middle of the period analyzed. Throughout, the regional patterns suggest greater convergence in the transition countries that joined the European Union in 2004 than in the other, lower-income transition economies.
Keywords: G32; L11; O12; P31; 330; Transition; convergence; market structure; competition; enterprise finance; enterprise restructuring; Unternehmensentwicklung; Unternehmensfinanzierung; Reorganisation; Marktstruktur; Übergangswirtschaft